Linguistics And Informatics, The Role Of Formal Grammar In Language Processing - Yakout BACHIR (Akofena)
Abstract: This research emphasizes the role of linguistic theory in fostering an interdisciplinary domain where linguistic principles merge with informatics techniques, specifically in the field of computational linguistics. The study aims to illustrate the interaction between these two domains in the processing of natural languages. It particularly focuses on the significance of formal grammars and their contribution to enhancing computational techniques and the performance of related systems. The research outlines the general framework from which linguistic theory has evolved, with a focus on establishing descriptive grammars of natural linguistic knowledge that serve as explanatory models of speaker competence, characterized by their precise formal formulation. It also sheds light on the early descriptive languages and the subsequent development of formal grammar theory, reflecting a progression in linguistic research towards a rational cognitive approach that has attracted the attention of engineers. Finally, it discusses efforts to use formal grammars, particularly context-free ones, to establish analysis models suitable for computational standardization.